2021
DOI: 10.3390/jcm11010194
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Applications of Lymphatic Vessel Visualization Using Photoacoustic Imaging and Augmented Reality

Abstract: Lymphaticovenular anastomosis (LVA) is a widely performed surgical procedure for the treatment of lymphedema. For good LVA outcomes, identifying lymphatic vessels and venules is crucial. Photoacoustic lymphangiography (PAL) is a new technology for visualizing lymphatic vessels. It can depict lymphatic vessels at high resolution; therefore, this study focused on how to apply PAL for lymphatic surgery. To visualize lymphatic vessels, indocyanine green was injected as a color agent. PAI-05 was used as the photoac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“… 148 , 150 Lastly, the imaged anatomical morphology has also been successfully matched to the surgical field. 149 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 148 , 150 Lastly, the imaged anatomical morphology has also been successfully matched to the surgical field. 149 …”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that 3D highresolution imaging and differentiation of lymphatic and blood vessels is possible along with DBF characterization. [145][146][147][148][149][150] Figure 7 shows example PAI images.…”
Section: Lymphatic Vessel Detection Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Several clinical laser-based systems such as the PAI-05 [59] and the iThera Medical MSOT Acuity [60] , [61] have also been used for lymphatic vessel imaging, producing high-resolution images. However, these systems are bulky or not portable at all, extra safety precautions are obligatory, and computationally intensive post-processing steps are needed [50] , [51] , [62] . This adds further challenges to the clinical implementation in multiple settings such as outpatient clinics and operating rooms.…”
Section: Discussionmentioning
confidence: 99%